Evaluasi Program Tahsin Qur’an dengan Menggunakan Model Goal Free Evaluation di Ma’had Al-Jamiah Iain Kendari - Yusnita Winaldea; Nurlathifah Thulfitrah B (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to evaluate the effectiveness of the Tahsin Qur'an program at Ma'had Al-Jamiah IAIN Kendari using the Goal Free Evaluation model. This evaluation emphasizes tangible results without being tied to the initial objectives of the program. This study uses a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that the program has had a significant positive impact: participants showed improved reading ability in hijaiyah letters, mastery of basic tajweed, and increased self-confidence and spiritual closeness to the Quran. The high level of participant attendance and consistent enthusiasm for learning indicate active involvement in the learning process. The program has also proven to be able to create a conducive and sustainable learning community, even though it is run voluntarily without financial incentives. Several recommendations for development include the provision of advanced classes, improvement of learning materials, and increasing reach and wider support. This evaluation confirms that the andragogy-based tahsin learning approach is highly relevant for Quranic education for adults and deserves further development.